Apoyo en la revisión de diseños y construcción de infraestructura en la Alcaldía de Sogamoso. - Tangua Moreno, Xilena (Universidad Antonio Nariño, 2023)
The degree project is carried out through the internship modality that focuses on the contributions that as Civil Engineers in the training process can contribute in a public or private company, in this case public such as the Mayor's Office of Sogamoso. Where a project is addressed is the rehabilitation of the pavement structure of Carrera 23 between streets 5 and 5a and Calle 5a between Carreras 23 and 24. This involves contributing to both technical and administrative tasks in the advancement procedures of the construction, in strict compliance with the approved designs and the corresponding modifications. These tasks include the generation of detailed reports that reflect the executed budget, as well as the performance of nuclear density tests to verify the density of the materials used in the subbase and granular base.